2019
DOI: 10.14639/0392-100x-2439
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rhinosinusitis with polyposis and serum vitamin D levels

Abstract: SUMMARYThe pathogenesis of chronic rhinosinusitis (CRS) is still unknown, but it is accepted that various inflammatory factors are responsible for the different CRS subtypes. Vitamin D3 has been shown to alter inflammatory mediators in some diseases and its deficiency might also be associated with CRS with nasal polyposis (CRSwNP). Herein, we investigated serum vitamin D3 levels in patients with CRSwNP and its association with disease severity. In a cross-sectional study, 166 cases with CRSwNP and 172 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…24 Vitamin D has a known immunoregulatory function, and epidemiologic studies have shown that vitamin D insufficiency is common in immune disorders and some infectious diseases. 17,25,26 Furthermore, vitamin D exerts an inhibitory action on the adaptive immune system. 27 A normal level of vitamin D suppresses the production of proinflammatory cytokines, and this has been shown in patients with congestive heart failure as well as in experimental bowel diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Vitamin D has a known immunoregulatory function, and epidemiologic studies have shown that vitamin D insufficiency is common in immune disorders and some infectious diseases. 17,25,26 Furthermore, vitamin D exerts an inhibitory action on the adaptive immune system. 27 A normal level of vitamin D suppresses the production of proinflammatory cytokines, and this has been shown in patients with congestive heart failure as well as in experimental bowel diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D has a known immunoregulatory function, and epidemiologic studies have shown that vitamin D insufficiency is common in immune disorders and some infectious diseases 17,25,26 . Furthermore, vitamin D exerts an inhibitory action on the adaptive immune system 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Bavi et al reported quite low levels of vitamin D in CRS with nasal polyps at 12.11 ± 6.27 ng/mL, while in the control group, the levels were 90 ± 17.18 ng/mL. There was a negative correlation between serum vitamin D3 level and the Lund-Mackay score (R = -0.66) [ 11 ]. Similarly, Chandrakar et al described vitamin D levels of 12.01 ± 7.29 ng/mL in cases, while in controls, the levels were 22.87 ± 14.95 ng/mL.…”
Section: Reviewmentioning
confidence: 99%
“…Numerous studies have demonstrated that vitamin D3 can suppress immune cell differentiation and cytokine production. Some studies indicate that local calcitriol and tacalcitol block the production/synthesis of pro-inflammatory cytokines interleukin (IL) 6 and 8 in fibroblast cultures and that local regulation of vitamin D in the sinonasal tissue during CRS may be independent of serum 25(OH)-D levels [ 11 ].…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, 1,25-dihydroxy vitamin D3 was shown to significantly inhibit the ongoing proliferation of activated B cells and the generation of plasma cells [13]. In CRSwNP patients, the level of vitamin D in peripheral blood was lower than that in healthy controls and negatively correlated with disease severity [14][15][16]. The secretion of some inflammatory mediators, such as eotaxin and matrix metalloprotease (MMP), could be decreased by vitamin D [17,18].…”
Section: Introductionmentioning
confidence: 99%